2012
DOI: 10.1051/radiopro/2012024
|View full text |Cite
|
Sign up to set email alerts
|

Photon energy absorption buildup factors of gaseous mixtures used in radiation detectors

Abstract: Gamma-ray energy absorption buildup factors of gaseous mixtures; neon (95%) + argon (5%), argon (95%) + acetylene (5%) , argon (95%) + methane (5%), argon (95%) + carbon dioxide (5%), methane (70%) + pentane (30%) and argon (90%) + methane (10%) were studied by Geometrical Progression (G-P) fitting for the photon energy range 0.015-15 MeV. It was found that the equivalent atomic number, Z eq of the gaseous mixtures sharply reduces after 1 MeV photon energy. The Z eq for the mixture of methane (70%) + pentane (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Var i ous re search ers have used geo met ric-progres sion (G-P) fit ting to de ter mine gamma ray buildup fac tors for al loys [6], fly-ash ma te ri als [8], con crete shield ing [5], brick ma te ri als [9], gas eous mix ture [10], thermoluminescent dosimetric ma te ri als [11], heavy metal ox ide glasses [12], and hu man or gans and tis sues [13]. These stud ies show that G-P fit ting is useful for es ti mat ing buildup fac tors.…”
Section: Introductionmentioning
confidence: 99%
“…Var i ous re search ers have used geo met ric-progres sion (G-P) fit ting to de ter mine gamma ray buildup fac tors for al loys [6], fly-ash ma te ri als [8], con crete shield ing [5], brick ma te ri als [9], gas eous mix ture [10], thermoluminescent dosimetric ma te ri als [11], heavy metal ox ide glasses [12], and hu man or gans and tis sues [13]. These stud ies show that G-P fit ting is useful for es ti mat ing buildup fac tors.…”
Section: Introductionmentioning
confidence: 99%
“…Harima et al made an extensive historical review and reported gamma-ray build-up factors [3]. Various researchers have investigated gamma-ray build-up factors of different materials such as concrete [8,9], gaseous mixtures [10], human tissues [11] and soils and ceramics [12,13] which showed that the GP fitting is a very useful method for estimating build-up factors. Recently, radiation shielding by fly-ash concrete [14] has been reported.…”
Section: Introductionmentioning
confidence: 99%